Peningkatan Kompetensi Keilmuan IOT Melalui Pelatihan Pengontrolan Perangkat IOT dengan Menggunakan Smartphone untuk Siswa SMK dan SMA di Kota Malang - Dahnial Syauqy; Yuita Arum Sari; Putra Pandu Adikara; Muhammad Aminul Akbar; Hurriyatul Fitriyah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The internet has encouraged the emergence of a new paradigm in the use of computing, marked by the emergence of devices that are connected to each other or known as the Internet of Things (IoT). One of the factors that contributed to the rapid emergence of "things" in the IoT network was the rapid development of chip technology and also increasingly varied wireless communication technology. With the emergence of the phenomenon of the development of IoT, especially those involving entrepreneurial opportunities in related fields, it is considered important to be introduced early on to students of vocational-high school equivalents in Indonesia. The activity was held in September 2019 at Filkom UB involving 41 participants from 6 schools of vocational-high school or equivalent. The activity succeeded in increasing the participant's understanding of the theory and also the practice of IoT where the participants' pre-test and post-test scores increased from an average of 61.6 to 92.9. The implementation of the activity was also declared successful from the results of the questionnaire. From a total of 425 answers, there were 17 STS answers, 39 TS answers, 205 S answers and 164 SS answers. Taking into account the positive and negative components, a recapitulation of 415 answers (98%) was found to be satisfied with the implementation of the activities.